Blasphemie vor den Toren zur islamischen Welt: Die Gesetzgebung der Johanniter auf Rhodos um 1500 - Sarnowsky, Jürgen (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2024)
Blasphemy at the gates to the Islamic World: the legislation of the Hospitallers on Rhodes around 1500 The term ‘blasphemy’ is today used as basis to justify repression and terror. Its roots go back to antiquity. While in the Old Testament everyone who blasphemes God or disregards the divine order is to be punished by death, the medieval concept of blasphemy is wider, including less severe ‘offences by the tongue’ which are prosecuted in different ways. The article discusses the accusation of blasphemy in the military orders, especially for the Hospitallers on Rhodes around 1500. Since the sources from the law courts and the inquisition are lost, the paper focusses on the normative sources, both on the statutes of the order as well as on the legislation for the order’s subjects. The Hospitallers used ‘blasphemy’ explicitly mainly for the ‘offences of the tongue’, both for their subjects as for the members of the order, partly punished with ‘mirror punishments’ like the splitting of the tongue. But heresy, apostasy, and sodomy appear at least implicitly as forms of blasphemy which were more severe and thus heavily punished, mostly by death. Muslim slaves were also threatened by lapidation when accused of blaspheming God, St Mary, the saints, the cross, etc. Since the legislation against blasphemy was intensified after 1480, it seems to have been an instrument of discipling the order’s subjects in times of external danger.